Role of Catheter Directed Thrombolytic Therapy in Acute Iliofemoral Deep Venous Thromboembolism - Hussien, Mohammad; Soliman, Ahmed; Shawky, Khaled Ahmed; Mohammed, Osama Sameh; Abdelhassib, Ayman Refaat; Algaby, Abdulaziz Zienulabeden; Abdelaziz, Ibrahim Sayed; Abdelmawla, Mohamed Hassan (Journal of Neonatal Surgery, 2025)
Background: IlioFemoral Deep Venous Thromboembolism )DVT( accounts for around one-fourth of all instances of DVT . An endovascular treatment with minimally invasive procedures is catheter-directed thrombolysis CDT restoring venous patency, hastening the recovery of acute symptoms. Objectives: to assess short term outcome of catheter directed thrombolytic therapy in acute ilioFemoral DVT treatment regarding improvement of clinical condition, assessment of benefits and hazards regarding utilizing CDT. Methods: Clinically: evaluation of limb state tenderness, pain, edema during the hospitalized period. Radiologically: lower limb venous duplex to follow up the venous state and the time of thrombolytic therapy of the affected veins on admission and will be repeated after 1and 6 month Venography under C-arm after completion of recombinant tissue plasminogen activator (TPA) injection to follow up any residual part of DVT and assess vein patency after 2 days. Total 28 patients of acute (ilioFemoral DVT) was included in this study. Results: This study showed that CDT is effective in treatment ilioFemoral DVT and giving better results than anticoagulant therapy. 92.6% of our patients had thrombus lysis while our bleeding complication rate of 17.9% with no mortality. Cases. Conclusion: The early use of CDT immediately after onset of ilioFemoral DVT associated with satisfactory results in restoring normal venous patency and significant lowering post thrombotic complication